Konflikt med državo in gospodarskimi subjekti - kdaj državne intervencije presegajo ustavne omejitve - Knez, Rajko (Podjetje in delo, 2025)
The article examines the assessment of restrictions on freedom to conduct business. This freedom is guaranteed by Article 74 of the Slovenian Constitution, as well as by Article 16 of the Charter of Fundamental Rights of the European Union. It is also safeguarded by the four fundamental freedoms of the EU internal market and by competition rules. However, this fundamental freedom is not absolute. Where grounds for restriction are identified-grounds which may fall under the concept of public interest, or under EU law, under the notion of overriding reasons relating to the public interest or mandatory requirements- a freedom to conduct business may be restricted, provided that the steps of the justification test are met. The Constitutional Court has developed a tailored proportionality test, which is not entirely identical to the justification test required under EU law. The article clarifies that the latter demands greater judicial engagement. Such a test narrows the legislature’s margin of discretion while, conversely, placing greater demands on judicial review, which should seek to delineate the boundary between the legislature’s broad discretion and less restrained judicial scrutiny.
Keywords: EU Charter of Fundamental Rights; freedom to conduct a business; javna korist; Listina EU o temeljnih pravicah; omejevalni državni ukrepi; overriding reasons in the public interest; Pravni spori; prevladujoči razlogi v javnem interesu; prilagojen test sorazmernosti; public interest; reasonableness test; restrictive state measures; svobodna gospodarska pobuda; tailored proportionality test; test razumnosti; Ustavno pravo